2016
DOI: 10.1111/1365-2745.12564
|View full text |Cite
|
Sign up to set email alerts
|

Effects of shading and simulated grazing on carbon sequestration in a tropical seagrass meadow

Abstract: Summary 1.There is an ongoing world-wide decline of seagrass ecosystems, one of the world's most efficient carbon sink habitats. In spite of this, there is a clear lack of studies experimentally testing the effects of anthropogenic disturbances on carbon sequestration of seagrass systems. 2. We assessed the effects of two disturbances of global concern on the carbon sink function in a five-month in situ experiment within a tropical seagrass (Thalassia hemprichii) meadow by testing the impacts of shading and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
55
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 62 publications
(68 reference statements)
9
55
1
Order By: Relevance
“…The continuous loss of seagrass areas [6] leads to a decline in natural carbon sinks [74,75], and to ensure efficient management, factors for high carbon storage capacity should be evaluated. Several environmental and seagrass-related factors have shown to be of importance, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The continuous loss of seagrass areas [6] leads to a decline in natural carbon sinks [74,75], and to ensure efficient management, factors for high carbon storage capacity should be evaluated. Several environmental and seagrass-related factors have shown to be of importance, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…At a larger scale perspective, the loss of seagrass biomass from coastal waters would affect a range of ecosystem services (Cullen‐Unsworth et al., ; Orth et al., ) such as sediment stabilization (Newell & Koch, ), the nursery habitat function (Heck, Hays, & Orth, ), and fisheries productivity (Nordlund, Unsworth, Gullström, & Cullen‐Unsworth, ). As seagrass beds are considered a major sink for atmospheric CO 2 (Kennedy & Björk, ), such loss of seagrass cover would decrease the carbon sequestration capacity of coastal seas (Dahl et al., ; Deyanova et al., ), eventually resulting in a decrease in the long‐term carbon storage (Mcleod et al., ). Furthermore, a loss and decay of biomass, especially the belowground parts, has also been suggested to promote the production of sulfide and methane gas emissions from the affected meadow (Lyimo et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Macreadie et al (2015) provide an example from Australia, where seismic testing in the 1960s damaged a series of Posidonia australis beds, leading to a loss of 72% of sediment C. Such "natural experiments" have the advantages of temporal and spatial scale, but do not allow the controlled understanding of causal drivers that a manipulative experiment permits. There are few experimental studies that explore the impacts of seagrass loss on C; the two most relevant (Macreadie et al, 2014;Dahl et al, 2016) found no C losses following small scale disturbances, which is in contrast to the findings of the natural experiment in Macreadie et al (2015). This suggests that disturbance may need to be large scale (in time and/or space) before an effect is found, or that there are site-specific factors not yet understood.…”
Section: Introductionmentioning
confidence: 88%